Investigating the Readiness of Students in Primary Teacher Education Program through Verbal, Model, and Mathematical Representations of Number Sets - Özge Yiğitcan Nayir, Gönül Kurt Erhan, Merve Koştur, Hacer Türkoğlu, Şeref Mirasyedioğlu (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
The aim of this study is to determine the readiness of the first year students in Primary Teacher Education Department about the number sets. In line with this aim, students were asked to express counting numbers, natural numbers, whole numbers, rational numbers, irrational numbers, real numbers, and complex numbers with verbal, model, and mathematical representations. This study was designed as a survey study which is a descriptive model. A total of 61 students at Primary Teacher Education Program at Faculty of Education in a private university in the province of Ankara, Turkey participated in the study on a voluntary basis. Content analysis method was used to analyze the data. Results showed that Primary Teacher Education students have low level of readiness in the number sets. It was determined that participants had difficulty in expressing number sets with models; they tended to define natural numbers and counting numbers verbally and they defined irrational and real numbers associating them with other number sets. Moreover, it was ascertained that they used verbal, model, and mathematical expressions interchangeably when expressing the number sets.